Role of Peripheral Chemoreceptors on Enhanced Central Chemoreflex Drive in Nonischemic Heart Failure - Pereyra, Katherin; Diaz-Jara, Esteban; Arias, Paulina; Bravo, Liena; Toledo, Camilo; Schwarz, Karla; Del Rio, Rodrigo (My University, 2023)
Heart failure (HF) is a prevalent disease in elderly population. Potentiation of the ventilatory chemoreflex drive plays a pivotal role in disease progression, at least in part, through their contribution to the generation/maintenance of breathing disorders. Peripheral and central chemoreflexes are mainly regulated by carotid body (CB) and the retrotrapezoid nuclei (RTN), respectively. Recent evidence showed an enhanced central chemoreflex drive in rats with nonischemic HF along with breathing disorders. Importantly, increase activity from RTN chemoreceptors contribute to the potentiation of central chemoreflex response to hypercapnia. The precise mechanism driving RTN potentiation in HF is still elusive. Since interdependency of RTN and CB chemoreceptors has been described, we hypothesized that CB afferent activity is required to increase RTN chemosensitivity in the setting of HF. Accordingly, we studied central/peripheral chemoreflex drive and breathing disorders in HF rats with and without functional CBs (CB denervation). We found that CB afferent activity was required to increase central chemoreflex drive in HF. Indeed, CB denervation restored normal central chemoreflex drive and reduced the incidence of apneas by twofold. Our results support the notion that CB afferent activity plays an important role in central chemoreflex potentiation in rats with HF.
Keywords: carotid body denervation; heart failure; rtn; central chemoreflex potentiation